Role of pharmacogenomics in the drug development - Suvarna, BS (Kathmandu University Medical Journal, 2010)
Individuals respond differently to drugs and sometimes the effects are unpredictable. Differences in DNA that alter the expression or function of proteins targeted by drugs can contribute significantly to the variation in the individuals responses. The use of pharmacogenomics is to identify genetic polymorphisms that predispose patients to adverse drug effects that, although they may occur in only a small subset of the people treated with a new medication, are sufficiently toxic to jeopardise further development of the drug for all patients. Given the potential value of knowing all the possible factors that influence the effects of new agents, it is likely that pharmacogenomics will have an increasingly important role in drug discovery and development. This article briefly reviews concepts that underlie the emerging fields of pharmacogenetics and pharmacogenomics, with an emphasis on the pharmacogenetics of drug metabolism. Although only a few examples will be provided to illustrate concepts and to demonstrate the potential contribution of pharmacogenetics to medical practice, it is now clear that virtually every pathway of drug metabolism will eventually be found to have genetic variation. Key words: Drug; genotype; pharmacogenetics; pharmacogenomics DOI: 10.3126/kumj.v7i2.2716 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 172-176